ATP‐Induced Emergent Circularly Polarized Luminescence and Encryption. (10th March 2022) - Fan, Huahua; Li, Kun; Tu, Tao; Zhu, Xuefeng; Zhang, Li; Liu, Minghua
Abstract: Biomimetic ATP‐driven supramolecular assembly is important to understand various biological processes and dissipative systems. Here, we report an ATP‐driven chiral assembly exhibiting circularly polarized luminescence (CPL) via the interaction of an achiral terpyridine‐based Zn II complex with nucleotides. It was found that while the metal complexes could co‐assemble with the nucleotides to form fluorescent assemblies, only a combination of furan‐substituted terpyridine complex and ATP showed an intense CPL with a dissymmetry factor ( g lum ) as high as 0.20. This means that the complex could recognize ATP using CPL as a readout signal, thus providing an example of ATP encryption. Interestingly, when ATP was transferred into ADP or AMP under enzymatic hydrolysis, the CPL decreases or disappears. Addition of ATP generates CPL again, thus producing an ATP‐induced CPL system. This work presents the first example of ATP‐induced CPL and encryption. Abstract : An achiral terpyridine‐based Zn II complex has been developed that forms fluorescent complexes with nucleotides, but only in the presence of ATP. A chiral assembly is generated that exhibits circularly polarized luminescence (CPL) with a g lum factor as high as 0.20. This discrimination of ATP from other nucleotides should allow applications in encryption.